Da'wah Strategy of Tablig Council at the Central Leadership of Muhammadiyah - Muh Muh. Mutaqin (CV. Syntax Corporation Indonesia, 2023)
After crossing a century of movement, Muhammadiyah has grown very rapidly. Muhammadiyah is one of the Islamic mass organizations whose existence is evenly distributed in almost all parts of Indonesia. There is hardly a single district/city in the country that is not entered by Muhammadiyah. In the early days of the establishment of Muhammadiyah, the Tablighi Council was an organizational field that was first established by K.H. Ahmad Dahlan to facilitate the focus and reach of da'wah. Now the challenges of the Tablighi Council are increasingly complex because more and more Muhammadiyah citizens must receive spiritual flush and formation in beribaddah. To provide services to Muslims in general and Muhammadiyah citizens in particular, the Tablig Council developed a da'wah strategy. The strategy was prepared at the Central Leadership Level which is the highest leader in Muhammadiyah. Then the results are applied at all levels of Muhammadiyah starting from the level of Muhammadiyah Branch Leaders (at the village level), Muhammadiyah Branch Leaders (at the sub-district level), Muhammadiyah Regional Leaders (at the district level), Muhammadiyah Regional Leaders (at the provincial level), to the level of Muhammadiyah Central Leaders. It is also used as a guide in the Muhammadiyah Business Charity (AUM) environment which includes Schools, Universities, Hospitals, Orphanages, Banking, and other AUMs managed by Muhammadiyah.